Work Readiness and Educational Experiences of Graduating Students from Technical and Vocational Education and Trainings (TVETs) in Nigeria - Lawal, Hammed (My University, 2025)
This thesis investigated the perceptions of educational experiences and work readiness among Technical and Vocational Education and Training (TVET) graduating students from Nigeria. The objectives were based on how the students in these programs perceive their educational experiences and their level of work readiness skills and if there are differences based on their demographic factors such as gender, grades, ages, and educational levels. The study employed quantitative method to analyze the self-reported data from 172 graduating students from post-secondary colleges, monotechnic institutions, polytechnics and universities of technology across Nigeria. The results of the findings revealed that students generally have positive perceptions of their experiences in the program coupled with internship work experience to have had an impact on their critical thinking, communication, teamwork, problem-solving, and technical skills. Specifically, internship work experience was found to significantly enhance the students' self-reported work readiness. On the other hand, the findings revealed relatively low satisfaction of some of the TVET educational activities in the area of incorporating industrial knowledge practices, providing effective feedback mechanisms, and career services support. Meanwhile, in terms of the level of work readiness skills possessed, students perceived themselves as more proficient in team and social skills, while reporting lower proficiency in information and technical skills. The study did not find demographic factors such as gender, age and educational levels to significantly affect work readiness, but academic performance (grade level) did show a positive relationship with work readiness of the students. These findings underscore the need to help graduating students’ transit smoothly into the Nigerian labor market by strengthening industry partnerships with TVET institutions targeted towards prioritizing practical experience opportunities and integration of information and technology skills into TVET studies and providing tailored career guidance. Further research is recommended to explore these areas of partnership strengthening and understanding the nuances of skill development and work readiness within specific TVET fields and industries.
Keywords: Vocational education, graduates, employability, work readiness, skills, competences, TVET, PBL, PjBL, work-based learning